PEMANFAATAN ABU SERBUK KAYU DAN SEMEN PORTLAND SEBAGAI FILLER PADA CAPURAN ASPHALT CONCRETE -WEARING COURSE - DONI RINALDI BASRI; Fitra Ramdhani; Faridhotul Apriliya Wardani (LPPM Universitas Abdurrab, 2022)
Waste from wood processing is often found in Pekanbaru City, so it needs to be utilized. This research utilizes sawdust and portland cement as alternative materials to replace filler in the manufacture of Asphalt Concrete-Wearing Course (AC-WC) mixture. The purpose of this study was to determine the characteristics of the Marshall test on the AC-WC layer using a combination of sawdust and Portland cement filler. The method used is laboratory experiments with the initial step of finding the KAO value (Optimum Asphalt Content) with fillers using rock ash. Followed by replacing the filler with a combination of sawdust and portland cement. Variations in the mixture of Portland cement and sawdust, namely 0%-0%, 15%-85%, 25%-75%, 30%-70%, 40%-60%, 50%-50%, and 100% -0%. The specifications used in this study are the 2018 Revision 2 Public Road Specifications. The KOA obtained is 5.5%. Then the Marshall test was carried out on each variation to get the stability value and the mixed density value. Marshall test results with the best filler variations in this study were 60% sawdust and 40% portland cement. It can be seen that based on the stability value of the composition, the highest stability value was 1,278.64 kg, the MQ value was 491.78 kg/mm ​​and the melting value was 2.60 mm so it was concluded that the best AC-WC quality in this study found filler variations. 40% portland cement and 60% sawdust.